Strategies to Improve the Competitiveness of Sustainable Palm Oil Commodities in Indonesia - Judijanto, Loso (West Science Business and Management, 2025)
This study examines strategies to improve the competitiveness of sustainable palm oil commodities in Indonesia through a qualitative analysis involving five key informants: a government policymaker, an industry association representative, a sustainability expert from an NGO, an academic researcher, and a smallholder farmer representative. Using in-depth interviews and thematic analysis, the research identifies six central themes influencing competitiveness: strengthening certification and standards, enhancing supply chain transparency, promoting technology and innovation, reforming policies and institutions, fostering stakeholder collaboration with smallholder inclusivity, and pursuing market diversification with value addition. The findings reveal that while certification and compliance with sustainability requirements are essential for international market access, challenges remain in supporting smallholders, improving institutional coordination, and adopting innovative technologies. The study concludes that sustainability should not be viewed merely as a compliance obligation but as a strategic driver of competitiveness. Integrating sustainability principles into policies, practices, and market strategies can position Indonesia as a global leader in sustainable palm oil production.